Dynamical downscaling of a multimodel ensemble prediction system: Application to tropical cyclones. (8th April 2020) - Kaur, Manpreet; Krishna, R. Phani Murali; Joseph, Susmitha; Dey, Avijit; Mandal, Raju; Chattopadhyay, Rajib; Sahai, Atul Kumar; Mukhopadhyay, Parthasarathi; Abhilash, Sukumarapillai
Abstract: This study attempts dynamical downscaling to improve north Indian ocean (NIO) tropical cyclone prediction from a global multimodel ensemble prediction system using weather research and forecasting (WRF) model. A total of 16 ensembles are used in the WRF simulations, these ensembles are bias‐corrected prior to downscaling for model climatological errors. The ensemble mean constructed from the output of all downscaled ensembles is analyzed for added value to global predictions. This mean is also compared against observation as well as high‐resolution (12 km) deterministic forecast from global forecast system (GFS). Two devastating NIO tropical cyclone cases of year 2017 which were not reliably predicted by global systems have been selected for this study. The results show that downscaled predictions well simulate the intensity and spatial distribution of the rainfall and relative vorticity associated with these cyclonic storms. The wind and temperature vertical profiles during cyclone mature stage are also captured more accurately than raw prediction and high‐resolution global deterministic forecast. The study affirms the adequacy of dynamical downscaling in predicting the cyclonic storms over global real‐time weather forecasting system. Abstract : Accurate and reliable warning of the storms is critical for community, the global forecast systems under‐predicted the tropical storms selected for the study. Bias‐corrected and dynamically downscaled multimodel ensemble prediction system (BC‐D‐ERP) gave better forecast for the spatial evolution and vertical structures of the cyclonic storms Mora and Ockhi at relatively higher‐spatial resolution.